MINAT PETANI MENGADOPSI SHARING ECONOMY PEER-TO-PEER LENDING SEBAGAI ALTERNATIF PEMBIAYAAN PERTANIAN - Hera Laxmi Devi Septiani; Ujang Sumarwan; Lilik Noor Yuliati; Kirbrandoko Kirbrandoko (MIX: JURNAL ILMIAH MANAJEMEN, 2021)
ENGLISHResearch on adoption of sharing economy in agribusiness is still scarce, particularly the research on adoption of peer-to-peer lending by farmers.  Some studies have shown that sharing economy offers benefits to the farmers, hence it is important to drive farmers to adopt sharing economy.  This study aims to investigate the factors that drive the behavioral intention of farmers to adopt sharing economy.  The form of sharing economy investigated in this study is peer-to-peer lending in farming funding.  This study uses variables of UTAUT2 to measure the acceptance toward technology used in sharing economy and Theoretical Model of Participation in the Sharing Economy to measure the acceptance towards the service of sharing economy itself.  Besides the variables of the aforementioned theories this study also includes new variables which are trust and values. The respondents of this research are 144 farmers in West Java, Indonesia who have not adopted peer-to-peer lending farming funding.  The data is analyzed using SEM, showing the results that there are three variables showing significant and positive correlation, which are hedonic motivation, price value and habit.   BAHASA INDONESIAPenelitian mengenai sharing economy di sektor agribisnis di Indonesia relatif masih sedikit, khususnya penelitian mengenai adopsi peer-to-peer lending oleh petani.  Beberapa penelitian mengenai sharing economy menunjukkan bahwa sharing economy memberikan manfaat bagi petani, oleh karenanya penting untuk mendorong adopsi sharing economy oleh petani.  Penelitian ini bertujuan untuk menggali faktor-faktor yang mendorong timbulnya niat berperilaku di kalangan petani untuk mengadopsi sharing economy.  Bentuk sharing economy yang diteliti di dalam riset ini adalah peer-to-peer lending dalam pembiayaan pertanian.  Studi ini menerapkan variabel-variabel dari teori utama UTAUT 2 serta Model Teoretis Partisipasi Sharing Economy masing-masing teori tersebut untuk menginvestigasi faktor-faktor pendorong niat berperilaku mengadopsi sharing economy dari sisi teknologi serta dari sisi layanan sharing economy-nya sendiri.  Selain variabel-variabel dari kedua teori di atas penelitian ini juga menambahkan variabel kepercayaan (trust) dan nilai-nilai (values).  Penelitian dilakukan di wilayah Jawa Barat, Indonesia,  dengan jumlah responden 144 petani yang belum mengadopsi sharing economy peer-to-peer lending. Hasil analisis data menggunakan SEM menunjukkan terdapat tiga variabel yang menunjukkan hubungan signifikan dan positif, yaitu motivasi hedonis (hedonic motivation), nilai harga  (price value), serta kebiasaan (habit).